"A man never cries": A mixed-methods analysis of gender differences in depression and alcohol use in Moshi, Tanzania. - Alena Pauley; Mia Buono; Madeline Metcalf; Kirstin West; Sharla Rent; William Nkenguye; Yvonne Sawe; Mariana Mikindo; Joseph Kilasara; Judith Boshe; Brandon A Knettel; Blandina T Mmbaga; et al. (PLOS Global Public Health)
Globally, gender differences are well-documented in alcohol use behaviors and MDD, yet these remain understudied in Moshi, Tanzania. Understanding gender-specific nuances of these conditions is crucial for developing effective and culturally appropriate mental health treatments. This study aims to investigate gender differences in MDD, alcohol use, and other aspects of mental well-being among patients at Kilimanjaro Christian Medical Centre (KCMC). Six hundred and seventy-six patients presenting for care at the KCMC Emergency Department (ED) and Reproductive Health Centre (RHC) were enrolled between October 2021 and May 2022. Patients were selected through systematic random sampling and completed quantitative surveys, including the Alcohol Use Disorder Identification Test (AUDIT) and the Patient Health Questionnaire 9 (PHQ-9). Nineteen patients were purposively chosen from the study population for in-depth interviews (IDIs) exploring alcohol use, gender, and depression. ANOVA, chi-squared tests, adjusted log-binomial regressions, and a linear regression model were used to analyze quantitative data in RStudio. A grounded theory approach was used to analyze all IDIs in NVivo. Average [SD] PHQ-9 scores were 7.22 [5.07] for ED women, 4.91 [4.11] for RHC women, and 3.75 [4.38] among ED men. ED women held the highest prevalence of MDD (25%) compared to RHC women (11%) and ED men (7.9%) (p < 0.001). Depressive symptoms were associated with higher AUDIT scores for ED men (R2 = 0.11, p < 0.001). Qualitative analysis showed that while present for women, social support networks were notably absent for men, playing a role in alcohol use. For men, alcohol was described as a coping mechanism for stress. Intersectionality of gender, alcohol use, and depression is influenced by sociocultural and behavioral norms in Moshi. As such, multi-layered, gender-differentiated programming should be considered for the treatment of substance use and mental health conditions in this region.